Continuous Fluorescent Sirtuin Activity Assay Based on Fatty Acylated Lysines - Zessin, Matthes; Meleshin, Marat; Hilscher, Sebastian; Schiene-Fischer, Cordelia; Barinka, Cyril; Jung, Manfred; Schutkowski, Mike (International journal of molecular sciences, 2023)
Lysine deacetylases, like histone deacetylases (HDACs) and sirtuins (SIRTs), are involved in many regulatory processes such as control of metabolic pathways, DNA repair, and stress responses. Besides robust deacetylase activity, sirtuin isoforms SIRT2 and SIRT3 also show demyristoylase activity. Interestingly, most of the inhibitors described so far for SIRT2 are not active if myristoylated substrates are used. Activity assays with myristoylated substrates are either complex because of coupling to enzymatic reactions or time-consuming because of discontinuous assay formats. Here we describe sirtuin substrates enabling direct recording of fluorescence changes in a continuous format. Fluorescence of the fatty acylated substrate is different when compared to the deacylated peptide product. Additionally, the dynamic range of the assay could be improved by the addition of bovine serum albumin, which binds the fatty acylated substrate and quenches its fluorescence. The main advantage of the developed activity assay is the native myristoyl residue at the lysine side chain avoiding artifacts resulting from the modified fatty acyl residues used so far for direct fluorescence-based assays. Due to the extraordinary kinetic constants of the new substrates (KM values in the low nM range, specificity constants between 175,000 and 697,000 M-1s-1) it was possible to reliably determine the IC50 and Ki values for different inhibitors in the presence of only 50 pM of SIRT2 using different microtiter plate formats.
Keywords: sirtuin 1; Coloring Agents; Sirtuin 1; Peptides; sirtuiny; Lysine; peptidy; lysin; sirtuin 3; barvicí látky; sirtuin 2; Sirtuin 3; Sirtuins; Sirtuin 2